2022
DOI: 10.1093/emph/eoac036
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of higher mesenchymal CD44 expression in the human lineage

Abstract: CD44 is an extracellular matrix receptor implicated in cancer progression. CD44 increases the invasibility of skin (SF) and endometrial stromal fibroblasts (ESF) by cancer and trophoblast cells. We reasoned that the evolution of CD44 expression can affect both, the fetal–maternal interaction through CD44 in ESF as well as vulnerability to malignant cancer through expression in SF. We studied the evolution of CD44 expression in mammalian SF and ESF and demonstrate that in the human lineage evolved higher CD44 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…One example is the evolution of the CD44 gene which is expressed in much higher levels in humans and the rhesus monkey than in other eutherian species tested. 21 CD44 is a hyaluronic acid receptor and its expression in the tumor stroma has been implicated in cancer malignancy. 30 , 31 Similarly, we have shown that GATA2 is a pro-invasibility transcription factor, meaning that a knockout of GATA2 in human SFs and ESFs leads to lower invasibility by both trophoblast as well as cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One example is the evolution of the CD44 gene which is expressed in much higher levels in humans and the rhesus monkey than in other eutherian species tested. 21 CD44 is a hyaluronic acid receptor and its expression in the tumor stroma has been implicated in cancer malignancy. 30 , 31 Similarly, we have shown that GATA2 is a pro-invasibility transcription factor, meaning that a knockout of GATA2 in human SFs and ESFs leads to lower invasibility by both trophoblast as well as cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of endometrial stromal fibroblasts: Cow ( Bos taurus ), dog ( Canis lupus ), cat ( Felis catus ), guinea pig ( Cavia porcellus ), horse ( Equus caballus ), rabbit ( Oryctolagus cuniculus ), sheep ( Ovis aries ), rat ( Rattus norvegicus ), SCID-CTRL and SCID-EVOL ESFs were obtained from fresh uterus samples. 21 2–3 mm uterus fragments were created using a scalpel and digested with 0.25% Trypsin–EDTA for 35 min at 37°C, followed by dissociation buffer (1 mg/ml collagenase, 1 mg/ml Dispase, 400 μg/mL DNase I) for 45 min at 37°C. Cell clumps were homogenized by passage through a 22-gauge syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum parsimony was calculated using the castor package (v1.8.0) 29 . For continuous ancestral state reconstruction, restricted maximum likelihood was used via the ape package (v5.8) 30 as in 31 .…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the results section, we used neoSF and monoiPSC RNASeq data generated in this study, as well as publicly available M. domestica single-cell RNASeq and bulk RNASeq data from previously published studies [ 19 , 28 , 42 ], for a comparative analysis to better understand marsupial pluripotency architecture. The published raw fastq files used in this study are described in Supplementary Table S4 and were downloaded from the NIH Sequence Read Archive (SRA).…”
Section: Methodsmentioning
confidence: 99%